Environmental literacy of ISCED 2 pupils in Poland - Svobodová, Silvie (Revija za elementarno izobraževanje, 2023)
Environmental literacy comprises environmental knowledge, attitudes, sensitivity, and responsible environmental behaviour. This study focuses on the environmental literacy of ISCED 2 pupils in Poland. The survey analysed the relationship between environmental literacy and its significant determinants. The connection between environmental literacy and the gender, school grade and leisure time of the respondents was determined. More than three hundred respondents took part in the testing. A moderately positive relationship between the dimensions of environmental literacy was demonstrated. Analyses have also shown that environmental literacy is significantly determined by gender, school grade and leisure activities, especially outdoor activities.
Keywords: okoljska pismenost; okoljska vzgoja; osnovne šole; Poljska; razlike med spoloma